2010
DOI: 10.1111/j.1365-2966.2010.16533.x
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the coronal-line region of active galactic nuclei: spatially resolved spectroscopy with theHubble Space Telescope

Abstract: We present an analysis of Space Telescope Imaging Spectrograph (STIS)/Hubble Space Telescope optical spectra of a sample of 10 Seyfert galaxies aimed at studying the structure and physical properties of the coronal-line region (CLR). The high spatial resolution provided by STIS allowed us to resolve the CLR and obtain key information about the kinematics of the CL gas, measure directly its spatial scale, and study the mechanisms that drive the high-ionization lines. We find CLRs extending from just a few parse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 151 publications
(299 reference statements)
7
73
2
Order By: Relevance
“…Under that condition, it is difficult to see any optical CL emission if their bulk is produced in the inner face of the torus. Moreover, the high spatial resolution studies conducted by Rodríguez-Ardila et al (2006) and Mazzalay et al (2010) show that Ty2 sources display strong [Fe vii], [Fe x], and [Fe xi] lines, with emitting regions extending to distances of a few hundred parsecs from the center in the case of NGC 1068, that is, well beyond the expected size of the putative torus. Moreover, a dusty CLR would produce a very weak CL spectrum because of the absorption of the incident continuum by dust at large U(H) (Ferguson et al 1997).…”
Section: Frequency Of the Coronal Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under that condition, it is difficult to see any optical CL emission if their bulk is produced in the inner face of the torus. Moreover, the high spatial resolution studies conducted by Rodríguez-Ardila et al (2006) and Mazzalay et al (2010) show that Ty2 sources display strong [Fe vii], [Fe x], and [Fe xi] lines, with emitting regions extending to distances of a few hundred parsecs from the center in the case of NGC 1068, that is, well beyond the expected size of the putative torus. Moreover, a dusty CLR would produce a very weak CL spectrum because of the absorption of the incident continuum by dust at large U(H) (Ferguson et al 1997).…”
Section: Frequency Of the Coronal Linesmentioning
confidence: 99%
“…Recent studies (Whittle et al 2005;Schlesinger et al 2009;Mazzalay et al 2010) have pointed to photoionization as the main driver for the CLs. Yet, we note that a detailed analysis of CL flux ratios, as done in Rodríguez-Ardila et al (2006) shows that photoionization alone is not enough.…”
Section: Frequency Of the Coronal Linesmentioning
confidence: 99%
“…Based mostly on optical studies, there is now convincing evidence of blueshifts of the highly ionized species with respect to the systemic velocity, as shown by, for example, Rodriguez-Ardila et al (2006) and Mullaney & Ward (2008). In a recent study, Gelbord et al (2009) used spectra mined from the SDSS catalog to select 63 AGN based on the strength of their [Fe x] λ6374 line emission.…”
Section: Samples Of Agn With Highly Ionized Linesmentioning
confidence: 99%
“…Gelbord et al (2009) Prieto et al (2005) showed that, in a small sample of Seyfert 2s, the region is extended from a few tens up to 150 pc, making it significantly less extended 384 M. Ward et al (Mullaney et al, in preparation). than the NLR. Furthermore, several studies of the HIL, for example recent work by Mullaney & Ward (2008), have shown that the 44 profiles of the HILs can often be deconvolved into several components, and that the broadest of these has a FWHM in between those of the BLR and the NLR (as typified by the [O iii] λ5007 line). Finally, a very recent study of HILs using HST+STIS data (Mazzalay et al 2010) confirms substantial blueshifts and also detects line splitting at the core of some galaxies.…”
Section: Samples Of Agn With Highly Ionized Linesmentioning
confidence: 99%
See 1 more Smart Citation